A Combinatorial Code for Gene Expression Generated by Transcription Factor Bach2 and MAZR (MAZ-Related Factor) through the BTB/POZ Domain - Kobayashi, Akira (American Society for Microbiology, 2000)
Bach2 is a B-cell- and neuron-specific transcription repressor that forms heterodimers with the Maf-related oncoproteins. We show here that Bach2 activates transcription by interacting with its novel partner MAZR. MAZR was isolated by the yeast two-hybrid screen using the BTB/POZ domain of Bach2 as bait. Besides the BTB/POZ domain, MAZR possesses Zn finger motifs that are closely related to those of the Myc-associated Zn finger (MAZ) protein. MAZR mRNA was coexpressed with Bach2 in B cells among hematopoietic cells and in developing mouse limb buds, suggesting a cooperative role for MAZR and Bach2 in these cells. MAZR forms homo- and hetero-oligomers with Bach2 through the BTB domain, which oligomers bind to guanine-rich sequences. Unlike MAZ, MAZR functioned as a strong activator of the c-myc promoter in transfection assays with B cells. However, it does not possess a typical activation domain, suggesting a role for it as an unusual type of transactivator. The fgf4 gene, which regulates morphogenesis of limb buds, contains both guanine-rich sequences and a Bach2 binding site in its regulatory region. In transfection assays using fibroblast cells, the fgf4 gene was upregulated in the presence of both MAZR and Bach2 in a BTB/POZ domain-dependent manner. The results provide a new perspective on the function of BTB/POZ domain factors and indicate that BTB/POZ domain-mediated oligomers of transcription factors may serve as combinatorial codes for gene expression.